An Analysis of the Effects of Work Ability, Work Supervision, and Personality on Employee Performance at PT Pelindo Multi Terminal, Belawan Branch - Maya Widiyanti; Juniarti Juniarti; Hasrul Azwar Hasibuan (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of work ability, work supervision, and personality on employee performance at PT Pelindo Multi Terminal Branch Belawan. A quantitative approach with a descriptive method was employed, and statistical analysis was conducted using SPSS version 26. The population consisted of all permanent employees totaling 98 individuals, and a saturated sampling technique was applied, in which the entire population was used as the research sample. The results indicate that work ability, work supervision, and personality each have a positive and significant effect on employee performance partially. Simultaneously, these variables also have a positive and significant effect on employee performance. The coefficient of determination of 82.5% suggests that employee performance is explained by work ability, work supervision, and personality, while the remaining 17.5% is influenced by other variables not examined in this study.